Long-term result of out-patient neodymium-doped yttrium aluminium garnet laser photocoagulation surgery for patients with epistaxis. Issue 1 (24th November 2015) - Zhang, J; Qiu, R; Wei, C
Abstract: Objective: To evaluate the long-term efficacy of out-patient neodymium-doped yttrium aluminium garnet laser photocoagulation surgery for patients with epistaxis. Methods: A retrospective clinical study was conducted. A total of 217 consecutive patients who presented with acute or recurrent epistaxis received neodymium-doped yttrium aluminium garnet laser photocoagulation treatment in an out-patient setting. Results: At three years, 94 per cent of acute epistaxis patients versus 88 per cent of recurrent epistaxis patients reported no bleeding. The outcome scores at 12 weeks and 3 years after treatment showed no significant differences between the 2 groups ( p = 0.207 and p = 0.186). However, there was a significant difference in outcome scores at four weeks after treatment ( p = 0.034). The median (and mean ± standard deviation) pain levels experienced during the laser operation (performed in an office setting) were 4.0 (3.75 ± 2.09) in the acute epistaxis group and 4.0 (3.83 ± 2.01) in the recurrent epistaxis group. Neither group had any complications. Conclusion: Neodymium-doped yttrium aluminium garnet laser photocoagulation is desirable in the treatment of both acute and recurrent epistaxis, and has long-lasting efficacy.